Ethyl 2-(4-chlorophenyl)-3-(2,4-difluorophenoxy)acrylate - Gong, Hai-Bin (International Union of Crystallography, 2008)
In the molecule of the title compound, C(17)H(13)ClF(2)O(3), the dihedral angles formed by the aromatic rings of the chlorobenzene and difluorobenzene groups with the plane of the acrylate unit are 48.85 (12) and 9.07 (14)°, respectively. In the crystal structure, molecules are linked by weak intermolecular C—H⋯O hydrogen-bond interactions, forming chains along the c axis.